Vorschriften für die Weihung zum König Georgiens - Otkhmezuri, Giorgi (Georgica, 2016)
In Georgia, similar to the civilised world, every legislative act − whether secular, ecclesiastical, or a monument of state law−was drawn up according to a specific diplomatic rule. The existence of a coronation ritual in Lazica, “received since ancient times,” is noted by the 6th-century Byzantine historians (Agathias, Procopius of Caesarea). Historical sources also confirm the existence of the institution of co-regency (co-option to the throne) in feudal Georgia, as well as a secondary coronation upon the commencement of a sole reign. In the coronation ceremony, the high nobility of Western Georgia played a major role. The “girding of the sword” upon the king by them symbolised the voluntary transfer of power. Queen Tamar altered the coronation rite. The historical realities recorded in the 13th-century document “The Rite and Order of Coronation of Kings” (e.g., the “girding of the sword” by the Amirspasalar/commander-in-chief) emphasise the supremacy of royal power. The coronation of Teimuraz II, described by Papuna Orbelyani (1745), indicates that the “Rite and Order” established in the 13th century functioned in a virtually unaltered form until the abolition of Georgian statehood (early 19th century).